2001
DOI: 10.1521/pedi.15.1.60.18643
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Personality Pathology in Patients with Generalized Anxiety Disorder, Panic Disorder with and without Agoraphobia, and Social Phobia

Abstract: The relationship between co-occurring personality disorders and anxiety disorders (panic disorder with or without agoraphobia, social phobia, and generalized anxiety disorder) was examined, taking into account the effect of major depression. This article describes findings for 622 participants in the Harvard/Brown Anxiety Research Project, a longitudinal follow-up study of DSM-III-R-defined anxiety disorders. A total of 24% of participants had at least one personality disorder, with avoidant, obsessive compuls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0
11

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(63 citation statements)
references
References 28 publications
3
49
0
11
Order By: Relevance
“…We see this as a strength of the study in spite of the fact that epidemiological data show that up to 50% of GAD patients also fulfil criteria for depression, other anxiety disorders and somatization disorders [7, 8, 9, 10]. Our goal was to test the efficacy of CBT in GAD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We see this as a strength of the study in spite of the fact that epidemiological data show that up to 50% of GAD patients also fulfil criteria for depression, other anxiety disorders and somatization disorders [7, 8, 9, 10]. Our goal was to test the efficacy of CBT in GAD.…”
Section: Discussionmentioning
confidence: 99%
“…This type of disorder has gained increasing scientific interest in recent years [2, 3]. Epidemiological studies have shown that GAD is one of the most frequent mental disorders, with co-morbidity rates of up to 50% [4, 5, 6, 7, 8, 9, 10]. …”
Section: Introductionmentioning
confidence: 99%
“…These findings are inconsistent with a simple severity hypothesis. Data from several recent studies [125][126][127] also challenge the severity hypothesis. In sum, although SAD typically is more comorbid with AVPD than with other PDs and AVPD more comorbid with SAD than with other anxiety disorders, in neither case is the relationship at all exclusive, nor close enough to support a simple severity hypothesis.…”
Section: Social Anxiety Disorder Versus Avoidant Personality Disordermentioning
confidence: 99%
“…Relatively few studies have examined long-term outcomes or diagnostic course for either SAD or AVPD, but the existing data indicate that both disorders (like many others) have relatively early onsets and a persistent course, albeit with variability in severity over time. [155,168] Both the Collaborative Longitudinal Personality Study [127] and Harvard/Brown Anxiety Research Project [125] found significant but not exclusive overlap in the longitudinal courses of SAD and AVPD. Moreover, the longitudinal courses of AVPD and OCD also overlapped, although not as strongly.…”
Section: Social Anxiety Disorder Versus Avoidant Personality Disordermentioning
confidence: 99%
“…It is associated with deterioration in education, work, and social relationships as well as with comorbid mental disorders, especially other anxiety disorders, depression, alcohol abuse and personality disorder. Social phobia is generally found to have the highest degree of comorbid personality disorders among the anxiety disorders (Dyck et al, 2001;Sanderson, Wetzler, Beck & Betz , 1994). It is estimated that only about 5-10 % among persons with social phobia seeks treatment for their condition and, if they do, they do so, on average, more than 15 years after its appearance (Keller, 2003).…”
Section: A Social Phobiamentioning
confidence: 99%